2015
DOI: 10.1080/15599612.2015.1059535
|View full text |Cite
|
Sign up to set email alerts
|

Axial-Stereo 3-D Optical Metrology for Inner Profile of Pipes Using a Scanning Laser Endoscope

Abstract: As the rapid progress in the development of optoelectronic components and computational power, 3D optical metrology becomes more and more popular in manufacturing and quality control due to its flexibility and high speed. However, most of the optical metrology methods are limited to external surfaces. This paper proposed a new approach to measure tiny internal 3D surfaces with a scanning fiber endoscope and axial-stereo vision algorithm. A dense, accurate point cloud of internally machined threads was generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The rapid 3D optical measurement of the internal threads becomes more important nowadays especially in the transportation (automobile) industry since the internally threaded holes in engine are crucial to the safety, longevity and efficiency of modern engines [12]. Our previous work demonstrated that a vision-based 3D reconstruction technique, called axial-stereo vision, could be used for the measurement of small internally threaded holes [13]. However, it only recovered very limited internal profile at the opening of the hole.…”
Section: Methodology and Experimentsmentioning
confidence: 99%
“…The rapid 3D optical measurement of the internal threads becomes more important nowadays especially in the transportation (automobile) industry since the internally threaded holes in engine are crucial to the safety, longevity and efficiency of modern engines [12]. Our previous work demonstrated that a vision-based 3D reconstruction technique, called axial-stereo vision, could be used for the measurement of small internally threaded holes [13]. However, it only recovered very limited internal profile at the opening of the hole.…”
Section: Methodology and Experimentsmentioning
confidence: 99%
“…Commonly, non-contact machines emit structured light [6], which is reflected back from the part and recaptured by the unit. Selecting the right device is not easy, and depends largely on the part being measured.…”
Section: Contact and Non-contactmentioning
confidence: 99%
“…Thus, the quality of the threads and their measured inner profiles are crucial for engine safety, performance, efficiency, and longevity. 16 , 17 There are various sizes of internally threaded holes in the automotive engine block; most of them are smaller than 1 cm diameter. In this study, an internally threaded hole (M8) is used as the metal object to test our approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, this device is still large in relation to the internally threaded blind hole in the engine block and could not accommodate the working range of 15 to 40 mm from the probe tip. 30 In our previous study, 17 an approach was proposed to measure the internal 3-D surfaces with an axial-stereo vision algorithm and a scanning fiber endoscope (SFE) of 1.2-mm outer diameter (OD). 31 A dense point cloud was generated for a few threads from only two forward-view images along the hole axis.…”
Section: Introductionmentioning
confidence: 99%